Deformation Characteristics and Safety Evaluation of the Throw Filling Soft Clay Cofferdam under Super-Historical Flood Conditions - Ping Jiang; Yong Huang; Zhipeng Tao; Junhua Zhu; Ning Wang; Jianwei Qiao (Advances in Civil Engineering)
Affected by super-historical flood, the surface deformation of throw filling soft clay cofferdam is obvious and the stability of the cofferdam slope is difficult to ensure. Relying on the cofferdam project of Jiangxi Xinjiang Shuanggang navigation power junction and according to the data of filed investigation and automatic monitoring, the Plaxis infinite element software is used to analyze the deformation characteristics and stabilities of cofferdam during the super-historical flood period, and the effective emergency reinforcement measures are presented. The results show that (1) the stability of cofferdam is controlled by downstream face slope of cofferdam during the super-historical flood period, and there is a most dangerous slide surface interpenetrating through the top to the toe of downstream face slope; (2) the stability of upstream face slope is influenced significantly by the water level fluctuation and it is reduced sharply during the water level decline process; and (3) real-time remote monitoring can effectively reflect the deformation and failure characteristics of cofferdam under the condition of super-historical flood level and provide early warning and prediction in time. The results and analyzing methods can be applied to analyze the similar projects excellently.